2014
DOI: 10.1002/elsc.201400098
|View full text |Cite
|
Sign up to set email alerts
|

Continuous multistep versus fed‐batch production of ethanol and xylitol in a simulated medium of sugarcane bagasse hydrolyzates

Abstract: Co-cultures for simultaneous production of ethanol and xylitol were studied under different operation bioreactor modes using Candida tropicalis IEC5-ITV and Saccharomyces cerevisiae ITV01-RD in a simulated medium of sugarcane bagasse hydrolyzates. Xylitol and ethanol tolerance by S. cerevisiae and C. tropicalis, respectively, was evaluated. The results showed that C. tropicalis was sensitive to ethanol concentrations up to 30 g/L, while xylitol had no effect on S. cerevisiae viability and metabolism. The best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…This finding suggests that K. oxytoca UM2‐17 redirected its metabolism towards biomass generation. These results contrast with those of Asenjo and Merchuk (1994), where yeast extract and peptone supplementation maintained alcohol production rate and improved 2,3‐butanediol production …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding suggests that K. oxytoca UM2‐17 redirected its metabolism towards biomass generation. These results contrast with those of Asenjo and Merchuk (1994), where yeast extract and peptone supplementation maintained alcohol production rate and improved 2,3‐butanediol production …”
Section: Discussionsupporting
confidence: 89%
“…These results contrast with those of Asenjo and Merchuk (1994), 38 where yeast extract and peptone supplementation maintained alcohol production rate and improved 2,3-butanediol production. [39][40][41][42] The 2,3-butanediol yield is dependent on the sugar concentration used in the fermentation medium 2 ; the suitable sugar concentration range to produce 2,3-butanediol with maximal yield was defined as 20-100 g L −1 of glucose or xylose, because exceeding 150 g L −1 causes cellular inhibition, probably due to accumulation of subproducts such as ethanol and acetate [ Fig. 1(a)].…”
Section: Discussionmentioning
confidence: 99%
“…At the same temperature (30ºC) and working in batch, Castañón–Rodríguez et al. using simulated hydrolysates of sugarcane bagasse hydrolysates, with C. tropicalis and S. cerevisiae , obtain higher overall yields in ethanol (YE/sO = 0.37 g/g) and xylitol (YXy/sO= 0.31 g/g) although less productivity in biomass. However, in this work at 50ºC the xylitol yield was higher when in the fermentation H. polymorpha was used.…”
Section: Resultsmentioning
confidence: 99%
“…Castañón‐Rodríguez et al. studied sequential batch culture using C. tropicalis and S. cerevisiae in simulated sugarcane bagasse. This showed that C. tropicalis was sensitive to ethanol concentrations above 30 g L −1 .…”
Section: Sequential Batch Culturementioning
confidence: 99%
“…C. shehatae was initially used for glucose and xylose fermentation before adding a high-ethanol-tolerant yeast, either S. cerevisiae or B. bruxellensis, for cellobiose fermentation [141]. Castañón-Rodríguez et al [143] studied sequential batch culture using C. tropicalis and S. cerevisiae in simulated sugarcane bagasse. This showed that C. tropicalis was sensitive to ethanol concentrations above 30 g L -1 .…”
Section: Single Bioreactormentioning
confidence: 99%